2018
DOI: 10.1159/000492469
|View full text |Cite
|
Sign up to set email alerts
|

Pacifiers, Thumb Sucking, Breastfeeding, and Bottle Use: Oral Sucking Habits of Children with and without Phonological Impairment

Abstract: Aims: The aim of this study was to describe the nutritive and non-nutritive oral sucking habits (breastfeeding, bottle use, pacifier/dummy/soother use, thumb/finger sucking) of preschoolers with and without phonological impairment, and to determine whether oral sucking habits are associated with the presence and severity of phonological impairment. Methods: We conducted a cross-sectional study of 199 Australian English-speaking preschoolers with and without phonological impairment. Preschoolers’ speech was dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…In contrast, Vieira et al [38] consistently reported associated ORs with 95% CIs alongside their p values. Baker et al [34] and Pereira et al [37] only reported p values.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Vieira et al [38] consistently reported associated ORs with 95% CIs alongside their p values. Baker et al [34] and Pereira et al [37] only reported p values.…”
Section: Resultsmentioning
confidence: 99%
“…Information is not provided on the interviewer or recording of these data. Barbosa et al [39] and Baker et al [34] distributed self-administered parent questionnaires. While all studies collected data on the presence and duration of feeding and NNS behaviours, only Barbosa et al [39] collected data on the frequency of bottle-feeding and pacifier use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations